Locating longitudinal study participants 10 years after last contact: Contemporary approaches to sample retention. Issue 4 (30th August 2022) - Dimakos, Christina; Loomis, Colleen; Gilmer, Alexis; Wright, Carrie; Christens, Brian D.; Pelletier, Janette; Peters, Ray DeV.
Abstract: Aims: Despite their advantages, longitudinal studies often face high rates of attrition. This study documents the extensive efforts associated with retaining a longitudinal cohort last contacted 10 years earlier. Method: We examine the processes and outcomes of attempts to reach 1736 individuals who have been part of a multiwave study about growing up in Ontario, Canada. Contact methods include email, phone, text, social media, postal mail, announcements in newspapers, subway stations, and music streaming services. Results: Challenges included a lack of consistent annual communication with participants, children moving out of the parental home, and changes in email addresses and phone numbers. The most effective contact method was phone; text messages and friend referrals were the least effective. Overall, 41.5% of the original sample was reached. Locating former research participants years later necessitated multiple and repeated contact attempts, and intensive human resources. Conclusion: Ten lessons for effective sample retention are discussed. In summary, reducing attrition depends on a comprehensive study design and an organized and flexible protocol that adapts to a study's ever‐changing needs.